2005
DOI: 10.1242/jeb.01664
|View full text |Cite
|
Sign up to set email alerts
|

Laminin and the malaria parasite's journey through the mosquito midgut

Abstract: During the invasion of the mosquito midgut epithelium, Plasmodium ookinetes come to rest on the basal lamina, where they transform into the sporozoite-producing oocysts. Laminin, one of the basal lamina's major components, has previously been shown to bind several surface proteins of Plasmodium ookinetes. Here, using the recently developed RNAi technique in mosquitoes, we used a specific dsRNA construct targeted against the LANB2 gene (laminin γ1) of Anopheles gambiae to reduce its mRNA levels, leading to a su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 34 publications
1
44
0
2
Order By: Relevance
“…It has been documented that the number of P. berghei parasites present in the midgut 24 h PF decreases gradually during the next 2 days due to immune responses (48,75). AgMMP1 could mask the parasite from mosquito immune attacks, as has been suggested for laminin (76) and other molecules of the ECM, such as collagen (77). Additionally, the protease could process effector molecules of the innate immune system, such as antimicrobial peptides (78,79) and the complement C3-like protein TEP1 (thioester-containing protein 1) (80), a very potent effector against bacteria and/or P. berghei.…”
Section: Discussionmentioning
confidence: 93%
“…It has been documented that the number of P. berghei parasites present in the midgut 24 h PF decreases gradually during the next 2 days due to immune responses (48,75). AgMMP1 could mask the parasite from mosquito immune attacks, as has been suggested for laminin (76) and other molecules of the ECM, such as collagen (77). Additionally, the protease could process effector molecules of the innate immune system, such as antimicrobial peptides (78,79) and the complement C3-like protein TEP1 (thioester-containing protein 1) (80), a very potent effector against bacteria and/or P. berghei.…”
Section: Discussionmentioning
confidence: 93%
“…The contact with components of the midgut basal lamina (collagen and laminin) is thought to trigger the differentiation of ookinetes into oocysts [18,19], but it is unclear how this interaction initiates the developmental progression into an oocyst stage (Table 1). Furthermore, several ookinete surface proteins have been shown to specifically interact with mosquito laminin, including P25/28, circumsporozoite-and TRAP-related protein (CTRP), and secreted ookinete adhesive protein (SOAP) [19].…”
Section: Ookinete Invasion and The Transition Into An Oocystmentioning
confidence: 99%
“…Furthermore, several ookinete surface proteins have been shown to specifically interact with mosquito laminin, including P25/28, circumsporozoite-and TRAP-related protein (CTRP), and secreted ookinete adhesive protein (SOAP) [19]. Additional experiments in which gametocytes or ookinetes survive and produce mature oocysts when injected into the hemocoel of either mosquitoes [20][21][22] or Drosophila [23,24] indicate that ookinete invasion is not an essential step for progression into the oocyst stage.…”
Section: Ookinete Invasion and The Transition Into An Oocystmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent RNAi study, for example, has revealed a crucial role for mosquito laminin in this process. RNAi-targeting of this gene resulted in loss of basal lamina integrity that decreased oocyst numbers by approximately 60% (18). Most recent RNAi studies, however, have targeted mosquito immune genes to unravel their role in parasite development.…”
Section: The Rnai Revolution Reaches Mosquitoesmentioning
confidence: 99%